The Bhutan Diary: the land of the thunder dragon - Chan, Margaret Kit Yok (Universiti Teknologi MARA, Sarawak, 2017)
A working visit to Bhutan at the invitation of Samtse College of Education, Royal University of Bhutan from 18 to 25 April 2017 was undertaken by Professor Dato Dr. Jamil Hamali, Rector of UiTM Sarawak, Associate Professor Dr. Margaret Chan, the regional representative of the International Organisation for Science and Technology Education for South East Asia (IOSTE) and Associate Professor Dr. Ling Siew Eng, a member of IOSTE. Bhutan is a small landlocked Himalayan country with fewer than one million inhabitants guided by the Gross National Happiness (GNH) which expresses a shift in consciousness regarding how Bhutanese strike a balance between material and non-material values, prioritizing the happiness and well-being of humans and all life. Arriving in spring, considered as the most beautiful time of the year, when the valleys are green with fresh vegetation and fruit trees blossoming amidst the mountainous landscape, it was indeed an unforgettable experience. Traditional architecture remains alive in Bhutan. The Bhutanese wear their national dress throughout the day. For men is the gho, a knee-length robe tied at the waist by a cloth belt known as kera. For the women, the kira is an ankle-length dress consisting of a rectangular piece of woven fabric, wrapped and folded around the body and is pinned at both shoulders usually with silver brooches and bound at the waist with a long belt. It is usually worn with a wonju (long-sleeved blouse) inside a short jacket or toego.